Interleukin-18 and its gene single nucleotide polymorphisms (SNPs) influence chronic hepatitis C progression - Said, Ebada M; Soliman, Mohamed S; Shousha, Hend Ibrahim; Rashed, Mohamed Sanad; Elazm, Abeer Abo; Aamer, Rania Zakaria; Kamel, Mai Hamed; Abdelsalam, Fatma Mohamed (The Journal of Infection in Developing Countries, 2018)
Introduction: Interleukin-18 (IL-18) is a pro-inflammatory cytokine that is induced by hepatitis C virus (HCV) infection. Inter-individual variations of IL-18 gene expression may alter HCV-associated liver injury. Variable single nucleotide polymorphisms (SNPs) have been detected within IL-18 gene sequence. Quantitative assessment of IL-18 plasma level and detection of genotype frequencies of 2 functional polymorphisms of its gene (-607 C/A and -137 G/C) were done to assess their impact on the severity of chronic hepatitis C (CHC). Methodology: Cases group (I) comprised 110 treatment naïve CHC Egyptian patients (78 Males and 32 Females, mean age = 40.7 ± 11.8 years) who underwent routine laboratory investigations. Assessment of plasma level of IL-18 was done by enzyme-linked immunosorbent assay (ELISA), detection of IL-18 gene polymorphisms at positions -607 C/A and -137 G/C by polymerase chain reaction sequence specific polymorphism (PCR-SSP) analysis and Liver biopsy with METAVIR scoring were done. The control group (II) comprised 90 healthy participants. Results: Plasma levels of IL-18 were significantly higher in cases than the control group. We found a statistically highly significant (p < 0.001) positive correlation between IL-18 plasma level and both METAVIR necro-inflammatory grade and fibrosis stage. The A/A allele at -607 position was significantly more frequent (p < 0.05) in patients with F ≤ 1. Conclusions: Higher IL-18 plasma levels are found in CHC patients and positively correlate with the severity of liver disease. The presence of A/A allele at -607 position of IL-18 gene promoter is associated with milder liver disease.